Доля навчальної літератури під час нацистської окупації України на території зони військової адміністрації - Титаренко, Д. (Краєзнавство, 2016)
У публікації розглянуто деякі аспекти адаптації, підготовки та використання навчальної
літератури під час нацистської окупації України на території зони військової адміністрації.
Охарактеризовано вплив окупаційних управлінських та пропагандистських структур, представників місцевої педагогічної громадськості на зміст та параметри використання навчальної літератури. In the paper the questions of adaptation, preparation and using of educational literature during
the Nazi occupation of Ukraine on the territories under military administration are considered. The
influence of the occupation administrative and propagandistic structures, representatives of local educational
community on the content and parameters of using the textbooks is characterized.
It is emphasized, that the edition of new educational literature for the population of the occupied
territories was not planned by the Nazis. This problem has become important at the process of renewal
the activities of educational institutions during the occupation. Soviet textbooks, which were claimed
as politically dangerous, mostly were withdrawed or changed. In the paper the examples of adaptation
of the Soviet pre-war educational literature to new requirements were described. Some textbooks were
prepared or published in Kharkiv, Sloviyansk, Mariupol. The providing of educational process with
learning and teaching materials was carried out through the publication of the so-called «school
pages» in a local periodical press and use of art literature and pre-revolutionary textbooks. В публикации рассмотрены вопросы адаптации, подготовки и использования учебной литературы в период нацистской оккупации Украины на территории зоны военной администрации. Охарактеризовано влияние оккупационных управленческих и пропагандистских структур,
представителей местной педагогической общественности на содержание и параметры использования учебной литературы.